CD8+ natural killer cells have a potential of a sensitive and reliable biodosimetric marker in vitro - Vokurková, D; Sinkora, J; Vávrová, J; Rezácová, M; Knízek, J; Ostereicher, J (Physiological research, 2006)
The aim of our work was to evaluate peripheral blood lymphocyte subsets as in vitro indicators of the received dose of ionizing radiation (biodosimetric markers) in the range of 3-20 Gy and to determine the appropriate time interval, during which a dose-dependent induction of apoptosis occurs upon gamma irradiation. In lymphocyte subsets characterized by double color surface immunophenotyping, four-color flow cytometry was used for visualizing cell death-associated increase in superficial phosphatidylserine exposure and cytoplasmic membrane permeability by fluorinated Annexin V and propidium iodide, respectively. No differences between sham-treated and lethal dose (7 Gy)-irradiated samples were observed upon 6 h cultivation in vitro. Ten and 18 h later, about 50 % of lymphocytes were apoptotic, but only the minority of them was in the late apoptotic phase. The only difference in radioresistance of the CD4(+)CD8(-) and CD4(-)CD8(+) lymphocyte subsets was seen upon 2-day cultivation when huge depletion of intact cells and prevalence of the late apoptotic population became obvious. A dose-dependence study in 16 and 48 h cultures confirmed the effectiveness of major T cell subsets as biodosimetric indicators. On the other hand, the minor CD8(+) subset of natural killer (NK) cells has been identified as a radiosensitive lymphocyte population the disappearance of which correlated with the received dose. We demonstrated that the CD3(-)CD8(+)NK subset can be used as a lethal/sublethal dose discriminator to 16 h cultivation. In addition, our data indicate that two-day cultivation followed by CD3/CD8 expression analysis in an intact lymphocyte population may provide a clue for low dosage biodosimetry.
Keywords: biologické markery; kultivované buňky; Cells, Cultured; reprodukovatelnost výsledků; CD4-pozitivní T-lymfocyty; Dose-Response Relationship, Radiation; Sensitivity and Specificity; tolerance záření; antigeny CD3; Humans; senzitivita a specificita; Immunophenotyping; časové faktory; buňky NK; imunofenotypizace; antigeny CD8; vztah dávky záření a odpovědi; CD4-Positive T-Lymphocytes; Radiation Tolerance; lidé; apoptóza; CD8 Antigens; Time Factors; Reproducibility of Results; CD4 Antigens; CD8-pozitivní T-lymfocyty; záření gama; CD3 Complex; antigeny CD4; CD8-Positive T-Lymphocytes; Biomarkers; Gamma Rays; Apoptosis; Killer Cells, Natural